PERSONAL JOURNAL WRITING: SELECTING THE ETHNOGRAPHIC METHOD FOR ENQUIRY - Lund, Darren E. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1985)
After identifying the need for additional research into the writing proeess, particularly relating to expressive writing in the form of personal journals, the researcher explicated his personal assumptions regarding some of the values of this mode of self-expression. The ethnographic approach to research was introduced, with key tenets and assumptions serving as a basis for the review of several specific qualitative studies of the composing process. Commentary on the suitability of this approach to the personal writing experience led to the conclusion that an ethnographic approach would be essential to account for the highly interactive and subjective nature of the journal writing episode. RÉSUMÉ Après avoir déterminé le besoin de recherches complémentaires sur le processus d'écriture, notamment en ce qui a trait à l'écriture expressive qui apparaît dans les journaux intimes, le chercheur a exposé ses hypothèses personnelles au sujet de certaines des valeurs de ce monde d'expression. L'optique ethnographique de la recherche est présentée, les principes et les hypothèses clés servant de base à l'analyse de plusieurs études qualitatives particulières du processus de composition. Les remarques sur l'à-propos de cette démarche pour l'écriture personnelle ont abouti à la conclusion qu'une optique ethnographiques est essentielle à la justification de la nature éminemment interactive et subjective de la rédaction d'un journal.